Efektivitas pelatihan ORS (Online Research Skills) untuk mendukung studi dan penelitian mahasiswa di UIN Maulana Malik Ibrahim Malang - Mufid Mufid; Ari Zuntriana (Al Maktabah, 2016)
The focus of this research is to evaluate the effectiveness of Online Research Skill (ORS) trainingprogram in supporting students to study and conduct their research at UIN Maulana MalikIbrahim Malang. The purpose is to explore how effective the ORS training in supporting theirstudy performance. This study used research quantitative method with Kirkpatrick model approachadded. Kirkpatrick Model is used to evaluate the effectiveness of ORS training program at the levelof participants’ reaction and participants training process. In general, the result of the study foundthat the training is effective, and by 86.5% have contributed to the achievement of training objectives.However, the training still needs some improvements, specifically the use of more advanced mediatechnology for the next courses. Thus, based on those results, the researchers recommend that the LIORScurriculum need to be revised/improved based on participants’ views and SCONUL curriculum.